2019
DOI: 10.1038/s41598-019-44154-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of natural and cultured Cordyceps by NMR spectroscopy

Abstract: Cordyceps , a type of Chinese herbal medicine that exhibits anti-angiogenesis and tumor growth suppression effects, has recently gained increasing popularity. However, high-quality, natural Cordyceps , such as Ophiocordyceps sinensis , is very rare and difficult to obtain in large amounts. Cordyceps is cultured instead of harvested from natural sources, but the quality with respect to the ingredients has not been fully studied. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Structures of adenosine and herierin III were elucidated via the obtained NMR spectral data, including 1D ( 1 H and 13 C NMR) and 2D NMR [correlation spectroscopy (COSY), heteronuclear single quantum correlation (HSQC), heteronuclear multiple bond coherence (HMBC)]. Spectral data are in agreement with those reported in the literature for structural elucidation of adenosine [ 30 ] and herierin III [ 31 ]. The complete NMR data assignments of both compounds were summarised in Additional file 1 .…”
Section: Resultssupporting
confidence: 74%
“…Structures of adenosine and herierin III were elucidated via the obtained NMR spectral data, including 1D ( 1 H and 13 C NMR) and 2D NMR [correlation spectroscopy (COSY), heteronuclear single quantum correlation (HSQC), heteronuclear multiple bond coherence (HMBC)]. Spectral data are in agreement with those reported in the literature for structural elucidation of adenosine [ 30 ] and herierin III [ 31 ]. The complete NMR data assignments of both compounds were summarised in Additional file 1 .…”
Section: Resultssupporting
confidence: 74%
“…Unknown bioactive components or the interactive actions of multiple compounds in CM may exhibit various pharmacological effects. Intriguingly, it is reported that C. militaris from nature does not contain trehalose based on NMR analysis by other groups [ 28 ], but CM examined in this study contains an extremely high concentration. Although the direct relationship to the biological activity of major metabolites such as trehalose in CM is not clear at present, it is possible that the amounts of secondary metabolites having the direct biological activity also may be affected by the hosts and growing condition.…”
Section: Discussionmentioning
confidence: 63%
“…The metabolomic analytical technique has been used to explore metabolome similarities and differences in O. sinensis products or related products. By 1 H NMR spectroscopybased approach, metabolic profiles of various products including wild O. sinensis from three geographical locations and cultivated mycelia derived from three origins [28], three types of natural Cordyceps (O. sinensis, Cordyceps militaris and C. nutans) and Paecilomyces tenuipe samples, and 2 types of cultured C. militaris samples in aqueous extracts [52], natural O. sinensis and commercial C. militaris in water-boiled and 50% ethanol-soaked extracts [29] were analyzed. Using LC-MS, the metabolome differences between wild O. sinensis and artificial cultured C. militaris were conducted [53], and the components of aqueous extract of artificial cultured C. sinensis were profiled with focusing on the polar compounds [54].…”
Section: Featured Metabolites and Their Potential Roles As New Quality Control Biomarkersmentioning
confidence: 99%